Diagnosing, Ameliorating, and Monitoring Soil Compaction in No‐Till Brazilian Soils - Peixoto, Devison Souza; Silva, Bruno Montoani; Godinho Silva, Sérgio Henrique; Karlen, Douglas L.; Moreira, Silvino Guimarães; Pereira da Silva, Alessandro Alvarenga; Vilela de Resende, Álvaro; Norton, Lloyd Darrell; Curi, Nilton (Agrosystems, geosciences & environment, 2019)
Core Ideas One‐time tillage increased soybean yield as a result of improving soil physical properties. Penetration resistance, air capacity, macroporosity, relative field capacity, and S index were the soil physical properties that best predicted soybean yield. The most sensitive soil physical properties for detecting structural related alterations were equally important for predicting soybean yield. Penetration resistance is the indicator that addresses no‐tillage soil compaction and its effect on soybean yield. Soil compaction can significantly reduce crop yield. Our objective was to identify the most sensitive soil physical property and process indicators related to crop yield using a Random Forest algorithm (RFA). This machine‐learning, decision‐making tool was used with field‐scale data from five soil management treatments designed to ameliorate compaction in no‐tillage (NT) fields. The treatments were: T1, NT for 10 yr (control); T2, NT with surface application of 3.6 Mg ha−1 of agricultural gypsum; T3, NT with subsoiling plus 1.44 Mg ha−1 of highly reactive limestone applied to a depth of 0.60 m; T4, NT planting following chisel plowing at a depth of 0.26 m; and T5, NT with subsoiling to a depth of 0.60 m plus 1.44 Mg ha−1 of surface‐applied, highly reactive limestone. Fifteen soil physical properties and processes related to growth and yield of soybean [Glycine max (L.) Merr.] were measured. Mechanical intervention, specifically subsoiling, improved soil physical properties and increased soybean yield cultivated following occasional tillage. The RFA ranked penetration resistance (PR), air capacity, macroporosity, relative field capacity, and the Dexter‐S index as the most sensitive soil physical indicators affecting soybean yield. Those indicators were also sensitive to changes in soil structure due to subsoiling. We conclude that the RFA was an effective tool for screening indicators and that those chosen can be effective for monitoring soil compaction and its effect on soybean yield. Penetration resistance may be used to guide on‐farm decision‐making regarding when and how NT soil compaction should be addressed.